Idiopathic Trigeminal Neuralgia: A Case Report - Lamba, Chetna Deep; Jain, Shruti (Homœopathic Links, 2018)
Trigeminal neuralgia (TN) is the most frequent type of neuropathic facial pain affecting one or more branches of trigeminal nerve. Here, a 51-year-old woman diagnosed with idiopathic trigeminal neuralgia (ITN) presented with complaints of pain over right side of the face with redness of the eyes and excessive lachrymation since 5 years with weekly acute episodes of shooting pain. Chelidonium was chiefly prescribed followed by few doses of Spigelia as per indications which provided adequate pain relief. The complaints flared up following stressful circumstances for which Pulsatilla was prescribed after detailed case taking. The frequency, duration and intensity of pain reduced after homoeopathic treatment. The need for conventional medicine was also reduced. This suggests positive role of individualised homoeopathy in the treatment of ITN. Further studies should be undertaken to evaluate the role of homoeopathy in ITN.
Keywords: trigeminal neuralgia; homoeopathy; case report; Naranjo criteria